Smallholder fruit development in Bure District, Ethiopia: Experiences from IPMS - Dessalegn, Yigsaw; Berhe, Kahsay; Hoekstra, Dirk; Mehari, Y.; Derso, T. (International Livestock Research Institute, 2010)
Bure district has a diverse ago-ecology, different soil types, a relatively long rainy season and a number of rivers and streams for irrigation. Therefore, it has suitable tract of land to grow temperate, subtropical and tropical fruit crops. In 2007, fruits were identified as a potential marketable commodity by the stakeholders participating in the IPMS project. They diagnosed that farmers had limited orchard management knowledge and skill and were growing locally available less productive and low quality fruit varieties. In addition, the linkage among fruit production stakeholders was very weak. Moreover, fruit seedlings from local seeds were only multiplied and distributed from the government fruit nursery and the supply was inadequate. Therefore, the quantity and quality of fruit produced in the district was still very low. The stakeholders also identified possible interventions along the value chain and subsequently intervened in capacity building (orchard management and propagation techniques), improved varieties introduction, input supply (established private nurseries, introduced grafting in government nurseries), stakeholders linkage and marketing of outputs. Thirteen (13) private fruit nurseries were established in four Peasant Associations (PAs) and in Bure town, which produced 68% of the seedlings in the district in 2008. Poor women and landless youth were also able to participate. The skill and knowledge of farmers, Development Agents (DAs) and experts improved through training and study tours which created linkages with new knowledge and capacity development actors. However, shortage of scion to multiply grafted fruit planting materials hampered mango and avocado expansion. i.e. only 3% of the mango and avocado seedlings in 2008 were grafted. Project partners are however addressing the issue by identifying alternative scion supply for avocado. Presently, 35% and 93% of the avocado seedlings raised for July 2010 planting, in the government and private nurseries, respectively, are grafted.